2021
DOI: 10.3389/fphys.2021.644897
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobials Affect the Fat Body Microbiome and Increase the Brown Planthopper Mortality

Abstract: Symbionts in the abdomen fat body of brown planthopper (BPH) play an important role in the growth and reproduction of their host, Nilaparvata lugens Stål (Hemiptera: Delphacidae). Thus, controlling BPH infection on rice by inhibiting symbionts with antimicrobials is feasible. However, the effect of antimicrobials on the microbiome in the fat body and the relationship between microbial community and mortality have not been fully elucidated. A decrease in the total number of yeast-like symbiotes in the fat body … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 50 publications
3
8
0
Order By: Relevance
“…Significant differences in microbial communities were found in the gut and the fat body in BPHs treated with toyocamycin, tebuconazole, and zhongshengmycin. A decrease in the total number of YLS in the fat body and elevated mortality was observed, and Serratia significantly increased in the gut and fat body [47,48]. In our results, after rifamycin treatment, Wolbachia and Cardinium decreased, Arsenophnus and Pantoea increased significantly, which may be because Arsenophnus and Pantoea were able to occupy the space left by Wolbachia and Cardinium quickly.…”
Section: Discussionsupporting
confidence: 50%
“…Significant differences in microbial communities were found in the gut and the fat body in BPHs treated with toyocamycin, tebuconazole, and zhongshengmycin. A decrease in the total number of YLS in the fat body and elevated mortality was observed, and Serratia significantly increased in the gut and fat body [47,48]. In our results, after rifamycin treatment, Wolbachia and Cardinium decreased, Arsenophnus and Pantoea increased significantly, which may be because Arsenophnus and Pantoea were able to occupy the space left by Wolbachia and Cardinium quickly.…”
Section: Discussionsupporting
confidence: 50%
“…oryzae, causing changes in bacterial communities (Wang Q. et al, 2021). While zhongshengmycin is effective in controlling plant pathogens, it can also affect the microbiome in the fat body through feeding behavior, which can influence the mortality of N. lugens (Shi et al, 2021). Frontiers in Physiology frontiersin.org…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that the maximum co-toxicity coefficient to the third instar nymphs of N. lugens can reach 2,813.04 when the compound ratio of pymetrozine and dinotefuran is 2:1, and the synergistic effect of the two mixtures is remarkable ( Wang et al, 2013 ). Additionally, zhongshengmycin, a fungicide, can inhibit symbiotic microorganisms in the fat body of N. lugens , thereby increasing the mortality of N. lugens ( Shi et al, 2021 ; Song et al, 2021 ). Thus, we propose a novel method of using a mixture of pymetrozine and a fungicide such as zhongshengmycin to control pests by inhibiting their symbionts.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, more systematic and abundant occurrences are those of Talaromyces spp. in the abdomen fat body and gut of the brown planthopper (Nilaparvata lugens) (Hemiptera, Delphacidae) in China [45,46], which deserves further investigation in view of the assessment of eventual functional relationships. Moreover, the occurrence of Talaromyces in low relative abundance resulted in the analysis of the endomycobiome of another planthopper species, Delphacodes kuscheli [57].…”
Section: Occurrence Of Talaromyces Spp As Insect Associatesmentioning
confidence: 99%